2021
DOI: 10.1155/2021/9926544
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Structural, and Optical Bandgap Characterization of Extracted ZnO Nanoparticles from Commercial Paste

Abstract: ZnO nanoparticles (NPs) were extracted from a commercial paste in both colloidal and precipitate forms. The Zetasizer analysis performed on the colloid showed ZnO NPs ranging from ∼30 nm to ∼100 nm. Thin films of ZnO were deposited on glass substrates by spin-coating technique from a mixture of the extracted colloid and precipitate. The scanning electron microscope (SEM) images showed uniformly arranged, mesoporous, and nanostructured ZnO particles of different shapes, with an estimated film thickness of 0.67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
5
6
0
Order By: Relevance
“…However, this irregular trend of the values of the lattice parameters found to be increasing and decreasing as doping concentration increases is similar to preceding reports by Babar [9], Lv et al [11], Abdou and Al-mokhtar [14] and Senol et al [33]. The values of the lattice parameters (a and c and their ration c/a) obtained for this work has been supported by the report of Belkhaoui et al [16], Nabil et al [20]) and Ara´ujo J´unior et al [34]. In an ideal wurtzite structure, the c/a ratio is given 1.633.…”
Section: Interplanar Spacing (D-spacing)supporting
confidence: 92%
See 1 more Smart Citation
“…However, this irregular trend of the values of the lattice parameters found to be increasing and decreasing as doping concentration increases is similar to preceding reports by Babar [9], Lv et al [11], Abdou and Al-mokhtar [14] and Senol et al [33]. The values of the lattice parameters (a and c and their ration c/a) obtained for this work has been supported by the report of Belkhaoui et al [16], Nabil et al [20]) and Ara´ujo J´unior et al [34]. In an ideal wurtzite structure, the c/a ratio is given 1.633.…”
Section: Interplanar Spacing (D-spacing)supporting
confidence: 92%
“…The Debye-Scherrer equation ( 7) was used to calculate the average crystallite size, D in nm, [14][15] were as equations ( 8) and ( 9) were used to calculate the dislocation density (δ) [20][21] and the Lattice strain, ε, [21][22] respectively:…”
Section: Figure 1: Diagram Showing the Synthesis Of The Mn Doped Zno ...mentioning
confidence: 99%
“…It was found that ZnO is strongly influenced by the treatments given such as thermal, solgel, hydrothermal, and PH. Based on those publications that thermal treatment has a crystallite size tendency in the range of 30-40 nm [49,50], sol-gel ∼20 nm [51], and PH effect ∼50 nm [51]. We suspect that this change in crystal size is strongly influenced by the setting of lattice parameters [52].…”
Section: Resultsmentioning
confidence: 83%
“…To understand the crystallographic irregularity within the crystal structure, the dislocation density is calculated for all the samples. 31 The dislocation density is the length of dislocation per unit volume in the crystal and it is in ascending order with the pH of the precursor solutions (Table I). This observation suggest that crystalline lattice is modified along with the morphological variation of the as obtained ZnO samples with the incorporation of defects in the crystals.…”
Section: Resultsmentioning
confidence: 99%